Hubungan Pengetahuan Dan Persepsi Body Image Dengan Kesiapan Siswi Menghadapi Menarche Dini - Azizah, Syabila Nurul; Elsanti, Devita; Sumarmi, Sumarmi (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: : To determine the relationship between the level of knowledge and perception of body image with readiness to face early menarche in Ledug State Elementary School students. Methods: This type of quantitative research with a descriptive analytical design, using a cross-sectional approach, cluster random sampling technique, a population of 128 female students and a sample of 56 female students. The instruments are a questionnaire on the level of knowledge about menstruation, a questionnaire on body image perception, and a questionnaire on readiness to face menarche. Univariate and bivariate data analysis using the chi square test. Results: The level of knowledge has a significant relationship with readiness to face early menarche with a p value of 0.004 (<0.05). Perceived body image has a significant relationship with readiness to face early menarche with a p value of 0.016 (<0.05). Conclusion: The level of knowledge has a significant relationship with readiness to face early menarche with a p value of 0.004 (<0.05). Perceived body image has a significant relationship with readiness to face early menarche with a p value of 0.016 (<0.05).